Kepelbagaian dialek dalam Bahasa Melayu: analisis tatatingkat kekangan - Zaharani Ahmad (Fakulti Sains Sosial dan Kemanusiaan.Universiti Kebangsaan Malaysia, 2006)
This paper aims to examine phonological alternations triggered by the syllable coda condition in six regional dialects of Malay, namely Johor Malay, Kedah Malay, Perak Malay, Melaka Malay, Kelantan Malay and Sarawak Malay. The analysis is couched in the constraint-based approach of optimality theory (henceforth OT). It is observed that most of the Malay dialects do not permit liquid segments occupying the syllable coda position. Illicit coda segments are commonly resolved by three general strategies, namely C-deletion, feature changing rules and segmental coalescence. Each dialect employs different strategies in resolving illicit codas, giving rise to phonological variations among dialects. In OT the prohibition of some segments in the coda is governed by a formal constraint generally referred to as CODA COND. The satisfaction of CODA COND by the above mentioned strategies compels a violation of MAX-IO, IDENT-IO and UNIFORMITY respectively. A dialectal variation in Malay is analyzed in this study as the result of each dialect imposing a different particular ranking on those universal well-formed constraints.